The Effect of a Combined Herbal Ointment (Pepper, Rosemary, Peppermint) on Low back Pain after Coronary Angiography - Rezvan Ghafarzadegan; Masoomeh Noruzi; Masoomeh Mousavi; Zeinab Alizadeh; mehdi harurani; Reza Ghafarzadegan; javad javaheri (Institue of Medicinal Plants, ACECR, 2017)
Background: Angiography is one of the most important diagnostic procedures of heart patients is that despite many advantages in the detection of coronary artery disease , has caused many problems for patients. To prevent these complications, the patient is recommended bed rest. Followed this situation, back pain occurred and low back pain is common among these patients. Objective: This study aims to assess the effect of topical herbal ointment on back pain in angiography patients. Methods: This study was a two groups randomized clinical trial, in which patients underwent coronary angiography were selected with available sampling and randomly divided into two groups (taking herbal ointment) and control (placebo) and on angiography day and one day later treated with herbal ointment (4 times a day) and before taking the ointment, and at the end of the second day, pain was measured by VAS scale. Results: In this study assessed 80 patients that received angiography. The mean pain score in the test group prior to the intervention was 4/05 with a standard deviation 2/24 and after intervention was 2/47 with standard deviation 1/66. pain score in the control group prior to the intervention was 3/52 with a standard deviation 1/93 and after intervention was 3/45 with standard deviation 1/82. Conclusion: With regard the results of this study we can conclude that this herbal ointment (pepper, rosemary, peppermint) can reduce low back pain in patients after angiography and we can use this ointment to increase patient comfort although more research with more samples is needed in this area to achieve a certain result.